Comprehension of Lifestyle Modification in Patient with Type 2 Diabetes Mellitus: A Kap Study - Malik, Suleman Elahi; Kanwal, Shaista; Haider, Iqbal; Javed, Javeria; Yasir Iqbal; Bibi, Sidra (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES The objective of this study is to assess the understanding of lifestyle modification in patients with Type 2 Diabetes Mellitus, including activity, diet, and weight loss (if obese), to explore the reasons which keep them away from adopting the recommended lifestyle modification and to evaluate the interpretation of common foods by Type 2 diabetics. METHODOLOGY This hospital-based cross-sectional study was conducted in the MTI - Khyber Teaching Hospital, Peshawar, from 1st October 2022 to 31st January 2023. A validated questionnaire recorded all the pertinent details regarding the demographic profile, presence of comorbid conditions, and comprehension of lifestyle changes like diet, physical activity, and attainment of normal body mass index (BMI). A p-value ≤0.05 was considered a test of significance in this study. RESULTS Three hundred and five (305) Type 2 Diabetics, including 196 (64.3%) females and 109 (35.7%) males, were recruited with mean age and HbA1c as 58.52 ± 10.3 years and 9.15 ± 2.1 %, respectively. About 67.2% of patients were from urban areas, while 32.8 % belonged to rural settings. Almost 55% of participants were on oral antidiabetic agents, 34.4% were on insulin therapy, and 10.2% were taking both insulin and oral antidiabetics. CONCLUSION General attitudes and behaviors toward lifestyle modifications in T2DM patients are highlighted in this study. Although there is awareness regarding the positive impact, patients still need to transform this aspect into tangible changes in behavior. Although geographical and socioeconomic statuses were considered variables, they were not found to be determinants in compliance with lifestyle changes in T2DM in our settings.